Classification of SMEs According to Their ICT Implementation - Laima Catherine Alfonso-Orjuela; Yezid Alfonso Cancino-Gómez; Julio Alberto Perea- Sandoval (International Journal of Technology, 2022)
Small and medium enterprises (SMEs) are firms that have a wide impact on the country’s economy in Colombia and contribute 28% of GDP, so it is essential to achieve the competitiveness of these organizations. The government has promoted plans to adopt information and communications technologies (ICT) at SMEs to increase their productivity and competitiveness. SMEs are organizations that lag behind in technology adoption. Several investigations have been carried out to characterize them, but no questions have been raised regarding the different types of SMEs that can be found according to their ICT implementation. This research aimed to determine the current usability and perception in the implementation of ICT and subsequently classify organizations based on these two factors. The results describe five types of SMEs: those that experience, those that have been negligent, those that lag behind, those that hesitate, and those that improvise. The data were collected in 2019, reflecting the state of SMEs before the lockdown due to the SARS-CoV-2 virus outbreak.